Proyecto centro deportivo y recreativo parque bosque municipal, Florida Valle del Cauca, Colombia - Pillimue-Cobo, María Julieta (My University, 2016)
El municipio de Florida, cuenta con una infraestructura deportiva y recreativa conformada entre otros, por el parque bosque municipal el cual presenta deficiencias en la operación, mantenimiento y sostenibilidad de los servicios. El “proyecto centro deportivo y recreativo parque bosque municipal, municipio Florida, Valle del Cauca, Colombia’, busca contar con autonomía, legal y financiera que garantice su operación y mantenimiento de manera sostenible. La generación de ingresos permanentes garantizara la contratación del personal administrativo y operativo necesario para la prestación de los servicios y por otra parte que permita realizar las inversiones para potencializar los servicios demandados.
The municipality of Florida has a sports and recreational facility formed among others by the city’s forest park, which presents deficiencies in the operation, maintenance and sustainability of its services. The project: “Florida’s forest park and recreational center” of the municipality of Florida, Valle del Cauca, Colombia; seeks to have legal and financial autonomy to ensure its operation in a sustainable manner. The generation of a permanent income stream will allow the hiring of a management and operations staff that is required to provide Florida’s community with its demanded services in such facility. In addition, it will allow its management department to make investments to enhance such services.
Keywords: Equipamiento; deporte y recreación; desarrollo sostenible; municipio; plan de empresa; MBA; Máster Universitario en Dirección y Administración de Empresas (MBA)